Effective Multidisciplinary Communication in Healthcare: Cooperative Documentation Systems - Schoop, M.; Wastell, D. G. (Methods of Information in Medicine, 1999)
To support multidisciplinary communication and cooperation in healthcare, cooperative documentation systems (CDSs) have been developed. However, in the current generation of systems, communication problems that can pose a serious threat to smooth and effective cooperation have occurred and remain to be addressed. This paper presents a set of features that need to be considered in the design of a new generation of CDSs to avoid breakdowns in communication and cooperation. Our approach is solidly grounded in linguistic and social theories and based on empirical investigations of communication patterns in multidisciplinary healthcare. It is argued that this work provides a theoretically rigorous approach to the design of CDSs that will enable effective multidisciplinary communication and cooperation in healthcare.
Keywords: Communication; Cooperation; Documentation; Communication Theory